2020
DOI: 10.1177/2321024920967843
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Households Vulnerability to Food Insecurity: Evidence from Southern Ethiopia

Abstract: This study examines the level and determinants of households’ vulnerability to food insecurity using feasible generalised least square method. Data were collected using structured questionnaires from a random sample of 574 households. Descriptive results indicated that the incidence, depth and severity of food insecurity were 68, 31 and 18 per cent, respectively, while mean vulnerability to food insecurity was 73.34 per cent. The mean level of vulnerability to food insecurity at Chencha (humid), Demba Gofa (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The high proportions of severe food insecurity were largely from Arba Minch (51%) and from Bukavu (39%). This does not come as a surprise because [38,39] stressed that food insecurity is a thorny issue in Arba Minch-Ethiopia, and that it can be determined by various parameters, such as poverty, climate change, political instability and conflicts and about 16% of the DRC population is suffering from severe food insecurity [40]. Furthermore, the high proportions of those sorting waste compared to those using organic waste as compost or livestock feed implies that there are other purposes or CBE practices under which households use sorted organic waste.…”
Section: Descriptive Resultsmentioning
confidence: 95%
“…The high proportions of severe food insecurity were largely from Arba Minch (51%) and from Bukavu (39%). This does not come as a surprise because [38,39] stressed that food insecurity is a thorny issue in Arba Minch-Ethiopia, and that it can be determined by various parameters, such as poverty, climate change, political instability and conflicts and about 16% of the DRC population is suffering from severe food insecurity [40]. Furthermore, the high proportions of those sorting waste compared to those using organic waste as compost or livestock feed implies that there are other purposes or CBE practices under which households use sorted organic waste.…”
Section: Descriptive Resultsmentioning
confidence: 95%
“…According to Asrat and Anteneh [ 6 ], about 13% of Ethiopian people live in drought–prone rural areas and many of these households suffer from chronic undernourishment and food insecurity. Food security research in the arid and semi-arid areas of Southern Ethiopia by Eshetu and Guye [ 14 ] indicated that the prevalence of food insecurity in these areas was 68%, and the average vulnerability to food insecurity was 73%. Similarly, about 64% of the sampled households living in North-eastern rift valley of Ethiopia, which is the other drought–prone area of Ethiopia, were found to be food insecure [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not Applicable 30 (10) Small family size is de ned as 1-3members in the household, moderate family size is de ned as 4-6 members in the household, large family size is de ned as 7 members and above in the household…”
Section: Consent For Publicationmentioning
confidence: 99%
“…In Ghana the prevalence of food insecurity is not different, it is reported that about 38.2 percent of Ghanaians experienced food insecurity [9]. Study shows that the major determinants of individuals vulnerability to food insecurity consist of clusters of risk factors that include demographic factors such as age of household head, family size, safety net programs, distance from healthcare facility and death of household members [10]. Central to these cluster of risk factors in the Ghanaian setting is the family.…”
Section: Introductionmentioning
confidence: 97%